Preferred study areas in a female residence hall in U.P. Diliman - De Luna, Erika Joyce G.
ABSTRACT The purpose of the study was to determine the preferred study areas of selected residents of a female residence hall in the University of the Philippines-Diliman and how these areas facilitate learning. The multi-method approach of the study involved the use of survey, photo documentation, and descriptive observation. Thirty-seven respondents were selected using convenience sampling. The instruments of the study included a survey questionnaire, DSLR camera, notebook and pen, and a laptop. Results showed that the bedroom was the preferred study area of the respondents. Comfort, appropriate lighting and ventilation, and low noise level, together with the ability of the bedroom to support their learning preference were the reasons why the respondents chose the bedroom as their preferred study area. Despite the inadequacies of the bedroom, the positive reaction of the respondents towards it made them use the space as a study area. This is because of all the spaces in the dormitory, they felt more motivated to perform academic-related task in the bedroom such as reviewing, reading, writing, and research.